TRADITIONAL EDIBLE MACROPHYTES OF IKOP LAKE - Dr. Ch. Nivanonee (International Journal of Modern Agriculture, 2021)
Traditional use of wild edible, aquatic plants (macrophytes) as food has been in practice since time immemorial. But it has been increasingly neglected due to the socio- economic changes and modernisation of life styles. Hence, the present study has been taken up to bring forth the idea of indigenous usage of various aquatic edible plants. Macrophytes are being consumed by a larger section of the global population and ensures both affordable food and nutritional security. The present study has been done in context to Manipur, where an enormous diversity of such aquatic plants constitute a significant part of rural diet of the inhabitants of Ikop Lake. The Ikop Lake is a freshwater, saucer shaped,natural lake. It is situated in the South- eastern part of Imphal at a distance of about 40 km with an area of 13.5 sq. km. in the Thoubal District, Manipur. It lies at an intersection of 93º 52’ to 94º05’ E longitude and 24º31’ to 24 º40’ N latitude and it is situated at an altitude of 772 m above the mean sea level. Adhering to the topic of the present study, eleven (11) macrophytic species were shortlisted describing the mode of consumption.